2020
DOI: 10.3390/agriculture10100446
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Bradyrhizobium sp. under Continental Conditions in Central Europe

Abstract: Soil samples from different locations with varied soybean cultivation histories were taken from arable fields in 2018 in East Germany and Poland (Lower Silesia) to evaluate the specific microsymbionts of the soybean, Bradyrhizobium japonicum, one to seven years after inoculation. Soybeans were grown in the selected farms between 2011 and 2017. The aim of the experiment was to investigate whether there is a difference in rhizobia contents in soils in which soybeans have been recultivated after one to seven year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
6
1
Order By: Relevance
“…However, the results found by Zamukulu et al (2018) in South Kivu in DR Congo and Ahmed et al (2006) in Pakistan found that yield and nodulation increased with increasing doses of mineral nitrogen fertilizer indicating a positive relationship between soil N and nodulation. The difference observed between our results and those obtained by certain authors such as Voisin et al (2013) and Griebsch et al (2020), could be explained by the fact that these different studies were described under different conditions. Indeed, Mendes et al (2003) report that the soybean response to nitrogen depends on several factors such as the efficiency of the Bradyrhizobium strain, the soybean variety and the initial soil nitrogen in the event of nitrogen supply in the form of mineral fertilizer.…”
Section: Correlation Among N Content In Soil Leaves and Seeds As Well As Soybean Yieldscontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the results found by Zamukulu et al (2018) in South Kivu in DR Congo and Ahmed et al (2006) in Pakistan found that yield and nodulation increased with increasing doses of mineral nitrogen fertilizer indicating a positive relationship between soil N and nodulation. The difference observed between our results and those obtained by certain authors such as Voisin et al (2013) and Griebsch et al (2020), could be explained by the fact that these different studies were described under different conditions. Indeed, Mendes et al (2003) report that the soybean response to nitrogen depends on several factors such as the efficiency of the Bradyrhizobium strain, the soybean variety and the initial soil nitrogen in the event of nitrogen supply in the form of mineral fertilizer.…”
Section: Correlation Among N Content In Soil Leaves and Seeds As Well As Soybean Yieldscontrasting
confidence: 99%
“…For soil N at site 1 and 2, it correlated positively with yield and number of nodules (P <0.05). These results seem to be in contradiction with those found in Europe by Griebsch et al (2020) who found no relationships between N supplied alone as inorganic fertilizer on nodulation and yield except when supplied in combination with P. Furthermore, Voisin et al (2013) found that N supplied as mineral fertilizer slowed down nodulation and a lower yield than the control. However, the results found by Zamukulu et al (2018) in South Kivu in DR Congo and Ahmed et al (2006) in Pakistan found that yield and nodulation increased with increasing doses of mineral nitrogen fertilizer indicating a positive relationship between soil N and nodulation.…”
Section: Correlation Among N Content In Soil Leaves and Seeds As Well As Soybean Yieldsmentioning
confidence: 56%
See 1 more Smart Citation
“…It had been already shown that Bradyrhizobium japonicum is able to survive for a long time under Central European soil and climatic conditions [13,34,35]. Madrzak et al, (1995) and our own preparatory work also demonstrated that rhizobia were present in Central Europe, even though soybeans have not been grown before [12,36]. Further, Narozna et al, (2015) and McDermott and Graham (1989) demonstrated that Bradyrhizobia have low mobility in soil [13,37].…”
Section: Effects Of Intercropping With Soybeans On Nodule Developmentsupporting
confidence: 66%
“…In this context, various preparations are available on the market, in liquid or powder form, as well as the already fully inoculated seed. Various studies have already demonstrated the presence of soybean-specific bacteria after a long time in Central European soils where seed inoculated soybean had been cultivated many years before [11][12][13]. Previous reports have indicated a strong to moderate correlation between intensity of nodulation and the associated nitrogen fixation and, thus, a higher grain yield or grain N content [14,15].…”
Section: Introductionmentioning
confidence: 99%